2014
DOI: 10.1093/brain/awu195
|View full text |Cite
|
Sign up to set email alerts
|

The modern pre-levodopa era of Parkinson's disease: insights into motor complications from sub-Saharan Africa

Abstract: Delaying the initiation of levodopa has been proposed to reduce the risk of motor complications in Parkinson’s disease. In a 4-year multicentre study in Ghana, Cilia et al. find that motor fluctuations and dyskinesias are predicted by disease duration and levodopa dose, but not by the duration of levodopa therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
211
3
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(240 citation statements)
references
References 61 publications
14
211
3
12
Order By: Relevance
“…This finding, together with the usual young disease onset of dyskinetic patients2, might support the notion of a neuroprotective effect of the cholinergic system on nigrostriatal dopamine‐containing neurons 49, 50, 51. In this study, we were not able to properly address a putative neuroprotective effect of the cholinergic system on nigrostriatal dopamine‐containing neurons and disease progression.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This finding, together with the usual young disease onset of dyskinetic patients2, might support the notion of a neuroprotective effect of the cholinergic system on nigrostriatal dopamine‐containing neurons 49, 50, 51. In this study, we were not able to properly address a putative neuroprotective effect of the cholinergic system on nigrostriatal dopamine‐containing neurons and disease progression.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, 40% of PD patients may develop enduring motor fluctuations1 such as levodopa‐induced dyskinesias (LIDs), which may be severely incapacitating. Young age at onset and high levodopa doses are known risk factors for its onset 2. At present, few therapeutic options exist for the treatment of LIDs.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supportive of a few studies indicating that early initiation of levodopa might be a risk factor for motor complications (Schrag & Quinn, 2000; Denny & Behari, 1999) but contrary to some other surveys suggesting that delaying the start of levodopa therapy is not associated with a smaller risk of motor complications in the long term (Scott et al., 2016; Cilia et al., 2014). Our results support the opinion that younger age at onset of PD seems to be a risk factor for motor complications per se (Hashim et al., 2014; García‐Ruiz et al., 2012; Bjornestad et al., 2016; Warren Olanow et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence suggesting that delaying the start of levodopa therapy might not be associated with smaller risk of motor complications in the long term (Scott et al., 2016; Cilia et al., 2014). The relationship between motor complications and distinct clinical motor phenotypes of PD has not been studied enough.…”
Section: Introductionmentioning
confidence: 99%
“…The ELLDOPA study, a multicenter placebo-controlled clinical trial, concluded that levodopa treatment did not accelerate the rate of PD progression and was possibly neuroprotective [22]. There is now compelling evidence that duration and severity of disease [23] and high dosages of levodopa [24] (but not duration of levodopa treatment) are major risk factors for inducing levodopa-induced dyskinesias. Although some investigators consider noncontinuous delivery of levodopa to be a risk factor for this complication, this has not been proven and is best considered a hypothesis.…”
Section: Monoamine Oxidase-b (Mao-b) Inhibitorsmentioning
confidence: 99%